Impact of Migration on the Economy in Tripura: Examining the Economic Impact of Migration in Tripura (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Economics is a social science devoted to the study of how people and societies get what they need and want. Or, in more formal language, economics is the study of how societies divide and use their resources to produce goods and services and of how those goods and services are then distributed and consumed.